Analisis Hubungan Asupan Protein, Zat Besi, Vitamin C, Status Gizi, dan Frekuensi Kemoterapi terhadap Kadar Hemoglobin Pasien Kanker Payudara - Faradillah, Gladys; Palupi, Khairizka Citra; Novianti, Anugrah (JURNAL RISET GIZI, 2025)
Background: Breast cancer is the most prevalent cancer in Indonesia and the leading cause of cancer-related mortality. Low hemoglobin levels are a common negative prognostic factor in cancer patients, influenced by chemotherapy, nutritional status, and deficiencies in hemoglobin-forming nutrients. Objective: This study aimed to examine the association between protein, iron, and vitamin C intake, nutritional status, and frequency of chemotherapy with hemoglobin levels in breast cancer patients, and to assess differences in the consumption of nutrient-rich food sources between patients with low and normal hemoglobin levels at Dharmais Cancer Hospital, Jakarta. Methods: A cross-sectional design was applied from 11 November to 6 December 2024 involving 90 purposively selected respondents. Data were collected through interviews using a semi-quantitative food frequency questionnaire (SQ-FFQ). Correlation analyses were performed using Pearson and Spearman tests, while differences were analyzed using the Mann–Whitney test. Results: Most respondents were in early elderly age (45–59 years). A significant and strong correlation was found between protein, iron, and vitamin C intake and hemoglobin levels (p=0.0001), while nutritional status (p=0.090) and frequency of chemotherapy (p=0.222) were not significantly associated with hemoglobin levels. Significant differences were found in the consumption of chicken (p=0.006), chicken liver (p=0.006), tempeh (p=0.046), spinach (p=0.010), guava (p=0.000), and papaya (p=0.032) between patients with low and normal hemoglobin levels. Conclusion: Indicating that protein, iron, and vitamin C intake were associated with hemoglobin levels, while nutritional status and chemotherapy frequency were not.